YSL3-mediated copper distribution is required for fertility, seed size and protein accumulation in Brachypodium. Issue 1 (9th February 2021) - Sheng, Huajin; Jiang, Yulin; Rahmati, Maryam; Chia, Ju-Chen; Dokuchayeva, Tatyana; Kavulych, Yana; Zavodna, Tetiana-Olena; Mendoza, Patrick N; Huang, Rong; Smieshka, Louisa M; Miller, Julia; Woll, Arthur R; et al.
Abstract: Addressing the looming global food security crisis requires the development of high-yielding crops. In agricultural soils, deficiency in the micronutrient copper significantly decreases grain yield in wheat ( Triticum aestivum ), a globally important crop. In cereals, grain yield is determined by inflorescence architecture, flower fertility, grain size, and weight. Whether copper is involved in these processes, and how it is delivered to the reproductive organs is not well understood. We show that copper deficiency alters not only the grain set but also flower development in both wheat and its recognized model, Brachypodium distachyon . We then show that the Brachypodium yellow stripe-like 3 (YSL3) transporter localizes to the phloem, transports copper in frog ( Xenopus laevis ) oocytes, and facilitates copper delivery to reproductive organs and grains. Failure to deliver copper, but not iron, zinc, or manganese to these structures in the ysl3 CRISPR-Cas9 mutant results in delayed flowering, altered inflorescence architecture, reduced floret fertility, grain size, weight, and protein accumulation. These defects are rescued by copper supplementation and are complemented by YSL3 cDNA. This knowledge will help to devise sustainable approaches for improving grain yield in regions where soil quality is a major obstacle for crop production. Copper distribution by a phloem-localized transporter is essential for the transition to flowering, inflorescence architecture, floret fertility, size, weight, and protein accumulation in seeds. Abstract : Copper distribution by a phloem-localized transporter is essential for the transition to flowering, inflorescence architecture, floret fertility, size, weight and protein accumulation in seeds.